Challenges of Monetary Policy during Crisis in the United Kingdom - Paduszyńska, Marta (Journal of Finance and Financial Law, 2018)
The topic of the presented study is about the monetary policy in the United Kingdom, included situation and challenges of this policy during crisis. This article presents the structure of the central bank of England as well as economic trends in years 2002–2016. Special attention has been devoted to the Quantitative Easing – unconventional monetary policy followed by central bank in the wake of financial crisis that began in 2007. The main purpose of the article is to show the impact of the financial crisis on the monetary policy in the United Kingdom and methods of dealing with its negative effects. Realisation of this will be studied literature and data compiled by the institutions involved in the discussed issue, especially reports prepared by the Central Bank of England. The financial crisis has had a negative impact on the real economy of the United Kingdom. It limited possibilities of household consumption and also possibilities of investment companies. Both of those, consumption and investment are important determinants of GDP.